2020
DOI: 10.1101/2020.02.28.969154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms preventing Break-Induced Replication during repair of two-ended DNA double-strand breaks

Abstract: DNA synthesis during homologous recombination (HR) is highly mutagenic and proneto template switches. Two-ended DNA double strand breaks (DSBs) are usually repaired by gene conversion with a short patch of DNA synthesis, thus limiting the mutation load to the vicinity of the DSB. Single-ended DSBs are repaired by Break-Induced Replication (BIR) that involve extensive and mutagenic DNA synthesis spanning even hundreds of kilobases. It remains unknown how mutagenic BIR is suppressed at two-ended DSBs. Here we de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…We therefore estimated mutation rates to understand if the mutational process is also impacted and variable across genetic backgrounds. DNA synthesis during mitotic recombination is considered to be mutagenic (39) and this effect is suggested to be amplified in heterozygous genomes (49,50). In the 169 MA lines, we identified 912 single nucleotide mutations (SNMs) and 14 multi-nucleotide mutations (MNMs), of which 83 and 2 are homozygous, respectively (Supplementary file 5).…”
Section: Mutation Rate Is Constant Across Heterozygous Diploid Backgroundsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore estimated mutation rates to understand if the mutational process is also impacted and variable across genetic backgrounds. DNA synthesis during mitotic recombination is considered to be mutagenic (39) and this effect is suggested to be amplified in heterozygous genomes (49,50). In the 169 MA lines, we identified 912 single nucleotide mutations (SNMs) and 14 multi-nucleotide mutations (MNMs), of which 83 and 2 are homozygous, respectively (Supplementary file 5).…”
Section: Mutation Rate Is Constant Across Heterozygous Diploid Backgroundsmentioning
confidence: 99%
“…By contrast, T-LOH events result from mitotic crossovers and break-induced replication (BIR) mechanisms frequently spanning large chromosomal regions greater than 100 kb (37,38). BIR is a homologous recombination (HR) pathway that repairs only one-ended DSBs and suppressed at two ended DSBs (39). Despite their high fidelity relative to other repair pathways, recent findings have demonstrated that HR pathways promote genome instability through an increased load of mutagenesis and chromosomal rearrangements (40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%